Immunological response against SARS-CoV-2: a review between the host and virus response (Research, Society and Development, 2020)
The host's effective immune response against SARS-Cov-2, including innate and adaptive immunity, appears crucial to controlling and fighting viral infection. However, unregulated immune responses can result in immunopathology and altered pulmonary gas exchange, leading to acute respiratory distress syndrome. Unfortunately, the pathophysiology and treatment, especially for severe COVID-19, are still unclear. Thus, the aim of this review was to demonstrate a brief overview of the innate and adaptive immune response developed by the human body in cases of SARS-Cov-2 infection. To this end, a systematic review of a qualitative character was carried out, in which scientific articles indexed in the Pubmed/Medline databases were used, as well as official documents produced by the World Health Organization and the Ministry of Health - Brazil. The bibliographic search showed 2827 results in the Pubmed/Medline databases, of these 42 were used for the writing of this work. According to the literature consulted, it can be concluded that the stimulation of an immune response in cases of SARS-Cov-2 is essential for the control and elimination of the virus, including components of the innate and adaptive immune response. However, it can be observed that many times the infection by SARS-Cov-2 produces an exacerbated immune response, with the excessive production of inflammatory mediators, which from the clinical point of view contributes to the therapeutic failure and evolution of the disease.